Design Of An Automatic Bell Warning System For Prayer Times In A Net Centric Computing Lab - Juhariansyah, Juhariansyah; Ritzkal, Ritzkal; Hendri Hendrawan, Ade (Journal of Robotics and Control (JRC), 2020)
The development of science and technology is now increasingly providing convenience in everyday life. Various household appliances to office work tools use electronic devices so that human work is much lighter and easier. As an example of the use of an Arduino microcontroller which is used as an automatic bell time warning bell control. This research wants to provide a solution to these problems by giving automatic prayer times. The formulation of the problem in research is. (i) How do you design and implement a set of prayer time warning bell system tools? (ii) How do you test the series of prayer bell alert system tools? There are several research objectives including the following. (i) Can design and implement a series of prayer time warning bell system tools. (ii) Can produce a test time series of prayer time bell alarm system tools. The method in this study includes (i) analysis consisting of needs analysis, and analysis of work methods, (ii) Design consisting of Hardware Design, and Network Design (iii) Implementation consists of Hardware Implementation, Software Implementation , (iv) Testing Consists of Real Time Clock (RTC) Testing, Dfplayer Testing, i2c LCD Testing, System Testing Results, Telegram Testing. This prayer time automatic alarm bell is equipped with a dfplayer module that can play mp3, or wav, sound file formats. So the call to prayer information can play well. And this warning bell system will provide a notification to the telegram when the call to prayer time has arrived.